miRNA genetic variations associated with the predisposition of oral squamous cell carcinoma in central Indian population - Shikha Tiwari; Ritu Pandey; Vinay Kumar; Saikat Das; Vikas Gupta; Rajeev Nema; Ashok Kumar (Non-coding RNA Research)
The disease burden of Oral Squamous Cell Carcinoma (OSCC) is rising day-by-day and is expected to rise 62 % through 2035. The chewing of tobacco, areca nut, and betel leaf, poor oral hygiene, and chronic infection are common risk factors of OSCC, but genetic and epigenetic factors also contribute equally. MicroRNAs (miRNAs) are comprised of small, non-coding endogenous RNA that regulate a plethora of biological activities by targeting messenger RNA through degradation or inhibition. Single Nucleotide Polymorphisms (SNPs) in miRNA genes can regulate the development and progression of OSCC. The present study aimed to determine the association between SNPs in miRNA genes (miRSNPs) with the risk of OSCC. A case-control study involving 225 histo-pathologically confirmed OSCC cases and 225 healthy controls was conducted, where 25 miRSNPs were analyzed by iPLEX MassArray analysis. A SNP rs12220909 in MIR4293 showed a highly protective effect (CC vs GG, OR = 0.0431, 95%CI = 0.005–0.323, p = 3e-6). Whereas three SNPs, namely, rs4705342 in MIR143 (CC vs TT, OR = 2.25, 95%CI = 2.00–2.53, p = 0.0008), rs531564 in MIR124 (CC vs GG, OR = 24.18, 95%CI = 3.22–181.37, p = 3e-6), and rs3746444 in MIR499 (AA vs GG, OR = 2.01, 95%CI = 1.32–3.05, p = 0.001) were significantly associated with a higher risk of OSCC. Additionally, NanoString-based nCounter miRNA expression profiling revealed that miR-499a (Log2FC = −1.07), and miR-143 (Log2FC = −1.56) were aberrantly expressed in OSCC tissue. Taken together, the above miSNPs may contribute to the high incidence of OSCC in central India. However, further studies with large cohorts and ethnic stratification are required to validate our findings.